Vaginal microbiome in the third trimester of pregnancy among women at Rahima Moosa Mother and Child Hospital - Emvula, Simon E E I (My University, 2021)
Background: The normal vaginal microbiome is an essential component in women’s health. Obstetricians should be knowledgeable on the composition of the vaginal microbiome of healthy asymptomatic pregnant women and the microbiome’s community state types (CST) that contribute to poor pregnancy outcomes. Objectives: To describe the composition of the vaginal microbiome of healthy pregnant women and their demographics, and to evaluate short-term pregnancy outcomes. Method: This was a prospective descriptive study. Vaginal swabs were obtained from 21 women in their late third trimester of pregnancy. The QIAamp DNA Mini Kit was used to extract the DNA. Polymerase chain reaction (PCR) with primers targeting the V3 and V4 region of the 16S rRNA gene was used to characterise the microbiome. The Greengenes database was used for the distribution of taxonomic categories. Results: Lactobacillus species were identified in 95.2%(n=20) of participants. By fuzzy clustering of Pcoa Bray Curtis distances we identified three CSTs based on the dominant microbiome: CST-III n=10 (L. inersdominated), CST V n=5 (L. jenseniidominated), CST IV n=6(Gardnerella vaginalis and anaerobes dominated). A high prevalence of Atopobium vaginalis(n=12) andFinegoldia Magna (n=16) was also noted. Obesity was associated with the prevalence of Prevotella species (p=0.048). Conclusion: Lactobacillus were the predominant species of the microbial community. Obesity was associated with a high prevalence of Prevotella species. There are a significant number of women with unrecognised STI’s and Group B Strep. These results may serve as a baseline for further microbiome studies during pregnancies, which could assist in predicting its ability to influence pregnancy outcome.
This research reported is submitted to the Faculty of Health Sciences, University of the Witwatersrand in partial fulfilment of the degree of Master of Medicine in Obstetrics and Gynaecology